Protective effect of crocin on liver toxicity induced by morphine - Mohammad Reza Salahshoor; Mojtaba khashiadeh; Shiva Roshankhah; Seyran Kakabaraei; Cyrus Jalili (Wolters Kluwer Medknow Publications, 2016)
Crocin, a bioactive molecule of saffron can be purely isolated from the saffron extract. It has different pharmacological effects such as antioxidant and anticancer activities. Morphine is an opioid analgesic drug. It is mainly metabolized in liver and causes devastating effects. It can increase the generation of free radicals. This study was designed to evaluate the protective role of crocin against morphine-induced toxicity in the mouse liver. In this study, various doses of crocin (12.5, 25 and 50 mg/kg) and crocin plus morphine were administered interaperitoneally once daily to 48 male mice for 20 consecutive days. These mice were randomly assigned to 8 groups of 6 each. The liver weight and histology, aspartate amino transferase, alanine aminotransferase, alkaline phosphatase (ALP) and serum nitric oxide levels were studied. The results indicated that morphine administration significantly decreased liver weight and increased the mean diameter of hepatocyte, central hepatic vein diameters, liver enzyme levels, and blood serum nitric oxide level compared to saline group (P<0.05). However, crocin administration significantly boosted liver weight and decreased the mean diameter of hepatocyte, central hepatic vein, liver enzymes and nitric oxide levels in all groups compared to the group received morphine alone (P<0.05). It seems that crocin administration could protect the liver damage induced by morphine. The antioxidant effect of crocin may be a major reason for its positive impact on liver parameters.